Colorectal Surgeons Teaching General Surgery Residents: Current Challenges and Opportunities - Schmitz, Connie C.; Chow, Christopher J.; Rothenberger, David A. (Clinics in Colon and Rectal Surgery, 2012)
Effective teaching for general surgery residents requires that faculty members with colorectal expertise actively engage in the education process and fully understand the current context for residency training. In this article, we review important national developments with respect to graduate medical education that impact resident supervision, curriculum implementation, resident assessment, and program evaluation. We argue that establishing a culture of respect and professionalism in today's teaching environment is one of the most important legacies that surgical educators can leave for the coming generation. Faculty role modeling and the process of socializing residents is highlighted. We review the American College of Surgeons' Code of Professional Conduct, summarize some of the current strategies for teaching and assessing professionalism, and reflect on principles of motivation that apply to resident training both for the trainee and the trainer.
Keywords: surgery residents; professionalism; graduate medical education; medical ethics; mentoring